The Effect of Pruning Age and Diurnal Variability on the Antioxidant Activity of Tea (Camellia sinensis (L.) O. Kuntz) Leaves in Organic Tea Farming - Yusuf Şavşatlı; Aysel Özcan; Muhammed İkbal Çatal; Emine Yurteri; Fatih Seyis (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out in Rize province in 2016, on fresh leaf samples collected from an organic tea plantation. In this study, the aim was to determine the effect of pruning age (1st year, 3rd year and 5th year following the last pruning) and diurnal variability on antioxidant activity and dry matter rate in tea leaves depending on shoot periods. When the pruning age was considered, the highest antioxidant activity was obtained from the plants which were in 5th pruning age in the 1st shoot period with 4991,1 μmol FeSO4/g dw. In terms of the same trait, the effect of pruning age on antioxidant activity during the 2nd shoot period was insignificant, while the highest antioxidant activity in the third shoot period was obtained from 1st pruning age with 7229.2 μmol FeSO4/g dw. As a general average, considering intraday collecting time, antioxidant activity in leaves collected in morning (07.00) and at noon (12.00) was very close to each other, while the collected leaves in the evening (17.00) had higher values. The dry matter rates obtained from the 1st, 3rd and 5th pruning ages were 23.45%, 25.23% and 25.45% respectively. When the shoot period was considered, the lowest dry matter rate was 20.17% in the first shoot period and the highest dry matter rate was 28.8% in the 2nd shoot period and high values were obtained from the leaves collected at noon.